Peran Roh Kudus dalam Teologi Injili: Antara Pneumatologi Biblika dan Gerakan Karismatik Kontemporer - Amirudin Amirudin; Lajib Lajib; Kristian Moses (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
The role of the Holy Spirit is one of the central aspects of Christian theology, particularly within Evangelical theology, which seeks to uphold a balance between biblical truth and spiritual experience. This study aims to examine the understanding of the Holy Spirit in Evangelical theology, with a specific focus on the relationship between biblical pneumatology and the expressions of contemporary charismatic movements. The approach used is a theological–descriptive study through an analysis of biblical literature, classical Evangelical theological works, and contemporary research on charismatic movements in Indonesia and around the world. The findings indicate that Evangelical theology understands the Holy Spirit primarily as a divine person who works in regeneration, sanctification, and ministry empowerment based on the authority of Scripture. Meanwhile, the charismatic movement emphasizes more phenomenological aspects of the Holy Spirit’s work, such as Spirit baptism, spiritual gifts (charismata), and manifestations of supernatural power. Theological tension arises when charismatic experiences do not always align with the strict Evangelical hermeneutical principles applied to Scripture. Nevertheless, both approaches offer important contributions: biblical pneumatology preserves a healthy doctrinal foundation, while charismatic spirituality reminds the church of the importance of the Holy Spirit’s dynamic power in contemporary ecclesial life. This study concludes that integrating biblical foundations with openness to the work of the Holy Spirit can enrich the understanding and praxis of the contemporary Evangelical church. The church needs to develop a balanced pneumatology that is rooted in Scripture yet responsive to the movement of the Holy Spirit within the changing contexts of time and culture.